The Decision Calculus of Terrorist Leaders - J. Tyson Chatagnier; Alex Mintz; Yair Samban (Perspectives on Terrorism)
This article contributes to the literature on terrorist group decision-making by introducing a new procedure, Applied Decision Analysis, in an attempt to understand how leaders of terrorist organizations make decisions. We examine twenty-three decisions taken by leaders of three terrorist organizations: Al-Qaeda, Hamas, and Hizballah. We also demonstrate the use of the Applied Decision Analysis procedure to uncover the "Decision DNA" or “decision code” of leaders of such organizations. After reviewing the results and insights derived from this analysis, we conclude with implications for policies to counter terrorism.